Indagini geomorfologiche e glaciologiche nella Terra Vittoria (seconda Spedizione del Programma Nazionale di Ricerche in Antartide, 1986-1987). Geomorphological and glaciological observations at Terra Nova Bay, Victoria Land (Second expedition of the Italian Antarctic Research Program, 1986/87) - BARONI, CARLO; OROMBELLI G. (1987)
During the second Italian Antarctic Expedition in 1986/87 geomorphological and glaciological researches have been carried out, mainly concerning Cenozoic glacial deposits, Holocene glacier fluctuations and Holocene raised beaches. Three main glacial drifts have been recognised, the oldest being associated with well developed red paleosol. The youngest drift all along the coastal belt is composed of till with a muddy matrix, locally rich in fragments of Pelecypods and Serpulids deposited by a grounded ice shelf. At Black Ridge a lateral moraine is present marking the boundary between the youngest and the older drifts, elsewhere identifiable only by weathering evidences. Holocene glacier fluctuations ha ve been recognised, particularly in the local alpine glaciers: On the basis of the relationships between moraines and raised beaches at least two glacial advances can be inferred in Late Holocene. Near Edmonson Point ice-cored moraines composed of fossiliferous beach sand and gravel testify an advance younger than 2 200 ± 45 yr B;P. Holocene beaches raised up to 30 m are well known at Terra Nova Bay (Inexpressible Island, Gerlache Inlet) . More to the North, raised beaches have been observed along the coast of Wood Bay, up to an elevation of about 7 m. Numerous new samples of organic remaines associated with the raised beaches (penguin guano and bones, Seal bones, Pelecypods, Barnacles and Corals) have been collected. 14C ages (not corrected) so far obtained range from 5 770 ± 60 yr B.P. to the present. Preliminary glaciological observations and measurements have been conducted on the Strandline Glacier and a geomorphological map at a scale 1:10 000 has been surveyed for an area of the Northern Foothills near the Italian Station. Reconnaissance geomorphological observations have been carried out in the area extending from the David Glacier to the Tinker Glacier and studies on periglacial and weathering forms have been pursued.